1993
DOI: 10.1111/j.1432-1033.1993.tb17818.x
|View full text |Cite
|
Sign up to set email alerts
|

The action of Trypanosoma cruzi trans‐sialidase on glycolipids and glycoproteins

Abstract: Addition of sialic acid residues in the human pathogen Trypanosoma cruzi glycoconjugates is mediated by a trans-sialidase and not by a CMP-sialic acid : glycoconjugate sialyltransferase. Incubation of trans-sialidase with N-[galact~se-'~C]acetyllactosamine and 0-linked oligosaccharides, Nlinked glycopeptides (both obtained from fetuin) or sialyllactose showed that the last three compounds were donors of sialic acid residues to the first one. Moreover, N-and 0-linked oligosaccharides in asialofetuin and asialom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 19 publications
1
42
0
3
Order By: Relevance
“…Studies of TS specificity have shown that the enzyme is able to sialylate unbranched terminal ␤Galp residues, and that substitutions near the Gal decrease the extent of sialylation (39,40). We have confirmed these findings by using the purified O-linked oligosaccharides that are the natural acceptors on the parasite surface.…”
supporting
confidence: 72%
“…Studies of TS specificity have shown that the enzyme is able to sialylate unbranched terminal ␤Galp residues, and that substitutions near the Gal decrease the extent of sialylation (39,40). We have confirmed these findings by using the purified O-linked oligosaccharides that are the natural acceptors on the parasite surface.…”
supporting
confidence: 72%
“…In addition, affinity-purified enzyme inhibited attachment and invasion of sialylated cells, but not of the sialic acid deficient mutant (Ming et al, 1993). The specificity of a2,3-linkage of the sialic acid was shown by the finding that adhesion and invasion were blocked by a2,3-linked sialyllactose but not its a2,6-linked counterpart (Vandekerckhove et al, 1992;Ferrero-Garcia et al, 1993;Scudder et al, 1993). Transialidase is also believed to mediate attachment and invasion by sialylating parasite glycoproteins expressing the Ssp-3 epitope which has been shown to be involved in these processes (Schenkman et al, 1991.…”
Section: Chagas' Diseasementioning
confidence: 95%
“…These glycoproteins are involved in the mechanisms of invasion of the mammalian cell (5). The oligosaccharides responsible for this action function as acceptors of sialic acid in a trans-sialidase reaction (3,6). Single GlcNAc units are linked to threonine (3) or are further substituted with galactose.…”
mentioning
confidence: 99%